Developing Of Writing Enrichment Book Based On The Local Wisdom Value Of Javanese Poetry (Geguritan) - Subagyo, Subagyo; Supriyanto, Teguh; Yusuf, Amin (Universitas Negeri Semarang, 2021)
Javanese poetry (geguritan) learning still does not get maximum attention because there are no (geguritan) books that are integrated with local wisdom values. This research is to integrate Javanese poetry (geguritan) with the value of local wisdom contained in the enrichment book. This study aims to develop an enrichment book for writing Javanese poetry (geguritan) containing the value of local wisdom; produce a valid enrichment book; test the acceptance of the enrichment book and test the effectiveness of learning to write geguritan using the developed enrichment book. This research uses the model of Research and Development (R and D)The results showed that The results showed that enrichment book was valid with a score of 3.10was valid with a score of 3.10; the acceptance test of this enrichment book is 77.56% and the learning effectiveness test using this enrichment book is effective with an average value of 87.63. Based on the results of the study, it can be concluded that the geguritan writing enrichment book is effective to be applied in elementary schools and is able to improve the quality of learning